Impact of Morphology of Conductive Agent and Anode Material on Lithium Storage Properties - Zhang, Xiaobing; Ma, Ji; Chen, Kezheng (Nano-Micro Letters, 2015)
In this study, the impact of morphology of conductive agent and anode material (Fe3O4) on lithium storage properties was throughly investigated. Granular and belt-like Fe3O4 active materials were separately blended with two kinds of conductive agents (i.e., granular acetylene black and multi-walled carbon nanotube) as anodes in lithium-ion batteries (LIBs), respectively. It was found that the morphology of conductive agent is of utmost importance in determining LIBs storage properties. In contrast, not as the way we anticipated, the morphology of anode material merely plays a subordinate role in their electrochemical performances. Further, the morphology-matching principle of electrode materials was discussed so as to render their utilization more rational and effective in LIBs.